Immediate Interventions After Surgery to Reduce Readmission for Upper Extremity Infections. (May 2022) - Fisher, Alec Hayes; Gandhi, Jigar; Nelson, Zachery; Pascuzzi, Caitlin; Donley, Sarah; Franco, Michael Joseph
Abstract: Upper extremity infections (UEIs), commonly caused by intravenous drug use and direct trauma to the hand, can be devastating. Many studies support hand therapy postoperatively to improve outcomes. This population of patients often experience increased returns to the emergency department (ED) for treatment, repeat surgery, poor function, and increased hospital expenditure. This is a 2-phase study to investigate and intervene on the care pathway for patients undergoing surgery for UEI at a single urban university hospital. For the first 6-month phase, all patients with UEI requiring surgery received the standard of care, including written discharge instructions, a scheduled follow-up, and a determination for hand therapy based on evaluation. During the second phase, over the following 6 months, all patients with UEI requiring surgery received an intervention before discharge, in addition to standard of care, including a scripted educational session on the importance of hand therapy by a resident physician, home exercise program instructions, and a referral to hand therapy before discharge. Outcome measures were assessed for 6 months. Outcome measures included follow-up, hand therapy attendance, ED visits for the same complaint, readmissions, and reoperations. Forty-seven patients were in the first control group without intervention and 41 patients were in the second intervention group. Of the control group, 43% attended a follow-up appointment, 2% attended hand therapy, and 45% presented to the ED, resulting in a total of 167 visits. Eleven presented to the ED and were readmitted for complications from surgery, all 11 required a second operation. In the intervention group, 54% attended a follow-up appointment ( P = 0.044), more patients attended hand therapy (22% P = 0.013), and 24% presented to the ED ( P = 0.047), resulting in 40 ED visits. Seven were readmitted for complications from surgery and 4 required a second operation ( P = 0.1). Early, simple intervention and education prove to be an effective method to decrease emergency department burden and healthcare expenditure for treatment of a challenging population. Although additional education and referral to hand therapy utilization do not change operation rates, it decreased returns to the ED, readmissions, and increased follow-up.